2008
DOI: 10.1021/pr800198w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of c-Src Tyrosine Kinase Substrates Using Mass Spectrometry and Peptide Microarrays

Abstract: c-Src tyrosine kinase plays a critical role in signal transduction downstream of growth factor receptors, integrins and G protein-coupled receptors. We used stable isotope labeling with amino acids in cell culture (SILAC) approach to identify additional substrates of c-Src tyrosine kinase in human embryonic kidney 293T cells. We have identified 10 known substrates and interactors of c-Src and Src family kinases along with 26 novel substrates. We have experimentally validated 4 of the novel proteins (NICE-4, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 46 publications
1
65
1
Order By: Relevance
“…Accompanied with advances of high-speed and high-resolution mass spectrometry, the technique of kinase substrate screening using proteomic strategy is quickly evolving (5)(6)(7). Mass spectrometry has been extensively used for kinasesubstrate interaction mapping (8) and global phosphorylation profiling (9).…”
mentioning
confidence: 99%
“…Accompanied with advances of high-speed and high-resolution mass spectrometry, the technique of kinase substrate screening using proteomic strategy is quickly evolving (5)(6)(7). Mass spectrometry has been extensively used for kinasesubstrate interaction mapping (8) and global phosphorylation profiling (9).…”
mentioning
confidence: 99%
“…Large-scale phosphoproteomics, however, does not typically reveal precise connections between protein kinases and their direct substrates (11,12). In recent years, there have been increasing attempts to develop mass spectrometry-based proteomic strategies for the identification of elusive kinase substrates (7,13,14). These attempts commonly used purified, active kinases to phosphorylate cell lysate (or fractions of cell lysate) in vitro, followed by mass spectrometric analysis to identify phosphoproteins.…”
mentioning
confidence: 99%
“…c-Src tyrosine kinase plays a critical role in signal transduction downstream of growth factor receptors, integrins and G protein-coupled receptors. Amanchy et al employed peptide microarrays approach and identified tyrosine phosphorylation sites in c-Src substrates (Amanchy et al, 2008). They designed custom peptide microarrays containing all possible tyrosine-containing peptides and their mutant counterparts containing a Tyr → Phe substitution from the identified substrates.…”
Section: Arrays-based Applicationmentioning
confidence: 99%